Contrasting movements and connectivity of reef‐associated sharks using acoustic telemetry: implications for management. Issue 8 (1st December 2015) - Espinoza, Mario; Lédée, Elodie J. I.; Simpfendorfer, Colin A.; Tobin, Andrew J.; Heupel, Michelle R.
Abstract : Understanding the efficacy of marine protected areas (MPAs) for wide‐ranging predators is essential to designing effective management and conservation approaches. The use of acoustic monitoring and network analysis can improve our understanding of the spatial ecology and functional connectivity of reef‐associated species, providing a useful approach for reef‐based conservation planning. This study compared and contrasted the movement and connectivity of sharks with different degrees of reef association. We examined the residency, dispersal, degree of reef connectivity, and MPA use of grey reef ( Carcharhinus amblyrhynchos ), silvertip ( C. albimarginatus ), and bull ( C. leucas ) sharks monitored in the central Great Barrier Reef (GBR). An array of 56 acoustic receivers was used to monitor shark movements on 17 semi‐isolated reefs. Carcharhinus amblyrhynchos and C. albimarginatus were detected most days at or near their tagging reef. However, while C. amblyrhynchos spent 80% of monitoring days in the array, C. albimarginatus was only detected 50% of the time. Despite both species moving similar distances (<50 km), a large portion of the population of C. albimarginatus (71%) was detected on multiple reefs and moved more frequently between reefs and management zones than C. amblyrhynchos . Carcharhinus leucas was detected less than 20% of the time within the tagging array, and 42% of the population undertook long‐range migrations to other arrays in the GBR. Networks derived for C. leucas were larger and more complex than those for C. amblyrhynchos and C. albimarginatus . Our findings suggest that protecting specific reefs based on prior knowledge (e.g., healthier reefs with high fish biomass) and increasing the level of protection to include nearby, closely spaced reef habitats (<20 km) may perform better for species like C. albimarginatus than having either a single or a network of isolated MPAs. This design would also provide protection for larger male C. amblyrhynchos, which tend to disperse more and use larger areas than females. For wide‐ranging sharks like C. leucas, a combination of spatial planning and other alternative measures is critical. Our findings demonstrate that acoustic monitoring can serve as a useful platform for designing more effective MPA networks for reef predators displaying a range of movement patterns.